Assessment of microbiological contamination in the work environments of museums, archives and libraries - Skóra, Justyna (Aerobiologia (Bologna), 2015)
Museums, archives and libraries have large working environments. The goal of this study was to determine microbial contamination in these work places and estimate the influence of microclimatic parameters and total dust content on microbial contamination. In addition, research included evaluation of ergosterol concentration and fungal bioaerosol particle size distribution. Numbers of micro-organisms in the air and on the surfaces in museums were higher (2.1 × 10(2)–7.0 × 10(3) cfu/m(3) and 1.4 × 10(2)–1.7 × 10(4) cfu/100 cm(2), respectively) than in archives and libraries (3.2 × 10(2)–7.2 × 10(2) cfu/m(3) and 8.4 × 10(2)–8.8 × 10(2) cfu/100 cm(2), respectively). The numbers of micro-organisms detected in the tested museums, archives and libraries did not exceed occupational exposure limits proposed by Polish Committee for the Highest Permissible Concentrations and Intensities of Noxious Agents at the Workplace. The concentrations of respirable and suspended dust in museum storerooms were 2–4 times higher than the WHO-recommended limits. We found a correlation between microclimatic conditions and numbers of micro-organisms in the air in the tested working environments. In addition, a correlation was also found between ergosterol concentration and the number of fungi in the air. Fungi were the dominant micro-organisms in the working environments tested. Particles within the dominant fractions of culturable fungal aerosols sampled from museum storerooms had aerodynamic diameters between 1.1 and 2.1 µm.